Comparative Evaluation of Fluoride Release From Two Different Glass Ionomer Cement and a Novel Alkasite Restorative Material - An in Vitro Study - Harpreet Singh; Shashi Rashmi; Swathi Pai; Sandya Kini (Association of Support to Oral Health Research (APESB), 2022)
Objective: To compare the fluoride release from Conventional Glass Ionomer Cement (GIC),  Resin Modified GIC (RMGIC), and Cention N Alkasite Material. Material and Methods: Forty- five disc-shaped specimens of three different restorative materials (Conventional GIC, RMGIC, and Alkasite material) were made and divided into 3 groups (n=15). Fluoride release was evaluated at the end of Day 1, 7, 14, and Day 28 using fluoride ion-selective electrode. Intergroup and Intra-group analysis was done using One-way ANOVA with a Post-hoc test. A p-value of <0.05 was considered statistically significant. Results: Cention showed more fluoride release (in parts per million) than GIC and RMGIC at increased time duration. However, at the end of day 1, there was lesser fluoride release with Cention, as compared with the other groups. Conclusion: The new Alkasite restorative material showed promising results in terms of fluoride release and is better than GIC and RMGIC at increased time duration.